2009
DOI: 10.4161/psb.4.3.8256
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide triggers specific and dose-dependent cytosolic calcium transients in Arabidopsis

Abstract: Equally, plants possess signal transduction networks that are highly conserved in terms of components which are also as sophisticated as that in their mammalian counterparts. 2 In the resting (un-stimulated) state, the cytosolic free Ca 2+ concentration [Ca 2+ ] cyt is ~200 nM and most of the cellular calcium is sequestered in cytoplasmic organelles such as the vacuole (100 mM), endoplasmic reticulum (ER) (1 mM), or the cell wall (1 mM). 3 This difference of many orders of magnitude in free Ca 2+ concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been reported that NO is involved in the ABA-induced antioxidant defence system and NO functions both upstream and downstream of Ca 2+ /CaM in plants ( Zhang et al ., 2007 ; Sang et al ., 2008 ; Aboul-Soud et al ., 2009 ). To establish a link between NO and ZmCCaMK in ABA signalling, the NO donor SNP was used.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that NO is involved in the ABA-induced antioxidant defence system and NO functions both upstream and downstream of Ca 2+ /CaM in plants ( Zhang et al ., 2007 ; Sang et al ., 2008 ; Aboul-Soud et al ., 2009 ). To establish a link between NO and ZmCCaMK in ABA signalling, the NO donor SNP was used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several motifs identified as binding sites for transcription factors (MADS domain factors, TCP, WRKY) were also found upstream of transcription start ( Figure 1 ). Of particular interest is the −1500 to −900 region where motifs putatively involved in the binding of MADS domain protein (CArG box) [44] and in signalling pathways for auxin and brassinosteroid (ARFAT) [45] , gibberellin (GADOWNAT and GARE) [46] , [47] , abscisic acid and calcium (ABRE-like motif) [48] , [49] and ethylene (ERE) [50] were found. In plants, regulatory elements usually tend to be highly clustered in the vicinity of the core-promoter elements, but can also be found all along the promoter [51] , [52] .…”
Section: Resultsmentioning
confidence: 99%
“…In animal cells, NO functions as a secondary messenger to mobilize Ca 2+ from intracellular stores (Galione ). NO can increase [Ca 2+ ] in tobacco and Arabidopsis , and this increase in Ca 2+ can be inhibited by a pretreatment with c‐PTIO, suggesting that the induction is specifically mediated by NO (Lamotte et al ; Aboul‐Soud et al ). This NO‐induced accumulation of Ca 2+ can be significantly blocked by inhibitors of the Ca 2+ channels in the membrane, including La 3+ and Gd 3+ , and less significantly blocked by the intracellular Ca 2+ channel inhibitor 8‐bromo cADPR.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…This NO‐induced accumulation of Ca 2+ can be significantly blocked by inhibitors of the Ca 2+ channels in the membrane, including La 3+ and Gd 3+ , and less significantly blocked by the intracellular Ca 2+ channel inhibitor 8‐bromo cADPR. This suggests that the plasma membrane channel‐mediated influx of Ca 2+ is the main contributor to the NO‐induced elevation in cellular Ca 2+ (Lamotte et al ; Aboul‐Soud et al ). Considering the time it takes for heat exposure to induce the accumulation of intracellular Ca 2+ and NO, it is reasonable to conclude that NO acts downstream of Ca 2+ in the regulation of plant HS signaling, suggesting that NO feedback could enhance the Ca 2+ ‐mediated HS signaling, via an unknown mechanism.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%